Changes in the types of patients in burn unit: A single center experience - Shuai Liu; Xiaoying Wang; Lifa Chen; Weiming Wang; Nana Song; Yang Lu (Elsevier, 2022)
Background: Burns are a common concern around the world, with the majority of cases happening in low- and middle-income nations. China is the largest developing country. With the unremitting efforts of domestic colleagues, China has taken the lead in the treatment of burn in the world. With the change of times, we have observed some noteworthy changes in the types of patients that have admitted our Burns and Plastic Surgery, the Affiliated Hospital of Yangzhou University. Methods: This retrospective observational study included brought into; all patients reached to our burn unit during 2013-2021. The gathered data were descriptively examined and statistically contrasted with each other year. Results: Of 4407 cases admitted to burn unit during 2013-2021, men constituted 56 % of such cases, with an average age of 47.3 ± 19.3 years. Moreover, among the patients hospitalized, January and February usually admit fewer than other months. Between 2013 and 2021, both the number of patients admitted to burn unit and the expense of their hospitalization rose yearly. The percentage of burn patients admitted to burn ward of our hospital is decreasing, especially during the period of serious Coronavirus disease (COVID-19) epidemic. We also observed that during the COVID-19 pandemic, patients with superficial masses also dropped off a cliff because of government controls. Conclusion: The diseases in the department show the trend of maximizing marginal disciplines, burn surgeons are facing a more complex challenge. Further research addressing the relationship between the change of patient types and economic and social development in burn department will help to foster better pinpoint hospitalization patients need, fine service for hospitalized patients.